From KNIP Building to Sarinah Mall Building: Societeit Concordia in Malang City 1900-1970 - Rizka Cahyaning Arifin Putri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article discusses the transformation of the function of the Societeit Concordia building in Malang City in 1900-1970. This building was originally the center of social activities of the European elite during the Dutch colonial period which reflected social segregation and a symbol of colonial power in urban planning. After Indonesian independence, the building shifted functions to house the Malang Regional Central Indonesian National Committee (KNIP) in the late 1940s, marking the appropriation of colonial space by national power. Entering the 1970s, the building began to be redirected to a new function as an economic space, which later developed into Sarinah Mall as part of the city's modernization and economic nationalization. The writing of this article uses a historical method that emphasizes the credibility of sources. The results show that the transformation of Societeit Concordia is a representation of the political, social and economic dynamics in postcolonial Malang City. The building not only changed its function physically, but also experienced changes in meaning in the collective memory of the city community. These findings emphasize the importance of adaptive conservation of historic buildings to keep them relevant to the times without losing their historical value.